Managing organizational change a multiple perspectives approach - Palmer, Ian 1957-; Buchanan, David A.; Dunford, Richard (McGraw-Hill, 2022)
"Since the previous edition of this book published in 2009, the organizational world has changed dramatically-the global financial crisis, fresh geopolitical tensions, environmental concerns, greater focus on corporate social responsibility, economic uncertainties, emerging new markets, dramatic technological developments, demographic shifts, changing consumer tastes and expectations. Add to that mix the growing significance of social media, where positive and critical views of organizations and their products and services can be shared instantly and globally with large numbers of people"--